PENERAPAN MODEL PEMBELAJARAN INKUIRI TIPE PICTORIAL RIDDLE DALAM BENTUK ANIMASI TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI SMA NEGERI 2 BATUSANGKAR - Fauziah Fauziah (Universitas Negeri Padang, 2014)
The research is done to know influence of implementation inquiry learning type pictorial riddle in animation form for the physics students result class XI IPA at SMAN 2 Batusangkar. The type of research is quasi exsperiment research. The Research of design is randomized posttest only control group design. The population in this research is all students of class XI IPA at SMAN 2 Batusangkar in academic 2013/2014. The take of sampel was selected by cluster random sampling technique. The research data includes the learning outcomes of the three domains. The research of data are cognitive domain, affective domain, and psychomotor domain. The data was analized with mean equality test at 5% significance level. Outcame of research conclude that there effect was of implementation inquiry learning type pictorial riddle in animation form for the physics students result class XI IPA at SMAN 2 Batusangkar of cognitive, affective, and psychomotor